Economic Behavior of the Bajo Balimu Buton Tribe of Southeast Sulawesi - Mualim, Rahmat; Wahjoedi, Wahjoedi; Nasikh, Nasikh (Journal of Applied Business, Taxation and Economics Research, 2024)
The purpose of this study was to explain the economic behavior of the Bajo Balimu community, South Lasalimu District, Buton Regency, Southeast Sulawesi. This research uses a qualitative research method with a phenomenological approach with 11 respondents from the Bajo Balimu community. The results showed that the economic behavior of the Bajo tribe is economic behavior that is closely related to the sea or marine. Commonly referred to as marine economic behavior. There are two types of economic behavior of the Bajo community, namely, production behavior and marine-based consumption behavior. Production carried out by the Bajo community is fishing, fish farming (cages), seaweed, mining sea sand, and so on. Fishing is the main and most prominent production of other types of production. There are seven sub-behaviors of community production, namely, production results (products), production factors, place and time of production, production process, marketing, income, and risk. The consumption behavior of the Bajo tribe is the behavior of spending or using goods or services obtained from fishing income to meet life needs. There are three sub-consumption behaviors of the Bajo community, namely, aspects of consumption characteristics, financial management, and basic needs